2017
DOI: 10.1016/j.impact.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide nanoparticle ingestion alters nutrient absorption in an in vitro model of the small intestine

Abstract: Ingestion of titanium dioxide (TiO2) nanoparticles from products such as agricultural chemicals, processed food, and nutritional supplements is nearly unavoidable. The gastrointestinal tract serves as a critical interface between the body and the external environment, and is the site of essential nutrient absorption. The goal of this study was to examine the effects of ingesting the 30 nm TiO2 nanoparticles with an in vitro cell culture model of the small intestinal epithelium, and to determine how acute or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
135
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 92 publications
12
135
1
1
Order By: Relevance
“…It was shown that titanium dioxide NMs with a diameter of 30 nm led to an decreased iron and zinc transport in cells . It was suggested that the transport mechanisms were disturbed by TiO 2 NM ingestion . This goes along with our findings, where decreased zinc and iron cellular concentrations were observed, even under nontoxic exposure conditions .…”
Section: Resultssupporting
confidence: 90%
“…It was shown that titanium dioxide NMs with a diameter of 30 nm led to an decreased iron and zinc transport in cells . It was suggested that the transport mechanisms were disturbed by TiO 2 NM ingestion . This goes along with our findings, where decreased zinc and iron cellular concentrations were observed, even under nontoxic exposure conditions .…”
Section: Resultssupporting
confidence: 90%
“…36 Meena et al 15 reported Based on the results from in vitro and in vivo experiments, it was found that TiO 2 NP could cause oxidative stress, inflammation, apoptosis, and pathological changes in organs such as the intestine and the liver. 4,38,39 In the present experiment, TiO 2 NP induced toxicity, apoptosis, and increased ROS levels in HepG2 and Caco-2 cells. HepG2 cells are an appropriate in vitro model for the study of polarized human hepatocytes, as they secrete various key proteins that are vital for the study of cytotoxicity induced by NPs.…”
Section: Discussionmentioning
confidence: 47%
“…[1][2][3] Titanium dioxide nanoparticles (TiO 2 NPs) are widely used in industries such as paper and also in plastics, paints, ceramics, cosmetics, water/air purifiers, agricultural chemicals, toothpastes, and sunscreens. 3,4 They are also used in the food industry as whiteners in sauces and creamers. 5 Due to the high use of this compound, the question arises whether TiO 2 NPs can cause harm to basic tissues such as the intestine (the site of NP absorption) and the liver (the site of NP metabolism and detoxification).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-known and widely used colorant is titanium dioxide, which accounts for 70% of the total production volume of pigments worldwide [6]. However, additional research on this topic is necessary to provide a good overview of the potential long-term negative effects associated with titanium dioxide nanoparticles [13,14]. Additionally, it is also used as a pigment in plastics, paper, inks, textiles, photovoltaic cells, biomedical devices, cosmetics, and even as a food additive [7,8].…”
Section: Introductionmentioning
confidence: 99%